1989
DOI: 10.1007/bf01907930
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal integrity during ischaemia and reperfusion of the isolated rat heart

Abstract: The effects of ischaemia and reperfusion on sarcolemmal permeability were studied in the isolated rat heart using an ionic lanthanum probe technique. Detection of increased permeability after exposure to short periods of ischaemia without accompanying reperfusion effects was achieved by employing a substrate-free, low calcium saline solution as vehicle for ionic lanthanum. Quantifiable results showed a rapid increase in sarcolemmal permeability in the subendocardium after 15 min of ischaemia, with the subepica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…After 15 minutes of NICA, lanthanum accumulated intracellularly, particularly in and around mitochondria, in the form of discrete spherical deposits of varying size in approximately 70% of the myocytes (Fig. 7b, actual data published in paper by Harper and Lochner, 1989). Results of La influx were qualitatively similar after 25 minutes of NICA (Fig.…”
Section: Vital Probing With Ionic Lanthanumsupporting
confidence: 66%
See 2 more Smart Citations
“…After 15 minutes of NICA, lanthanum accumulated intracellularly, particularly in and around mitochondria, in the form of discrete spherical deposits of varying size in approximately 70% of the myocytes (Fig. 7b, actual data published in paper by Harper and Lochner, 1989). Results of La influx were qualitatively similar after 25 minutes of NICA (Fig.…”
Section: Vital Probing With Ionic Lanthanumsupporting
confidence: 66%
“…This may be a misleading assumption as glutaraldehyde has recently been shown to alter natural membrane permeability in muscle (Harper, 1986). Unable to obtain credible results using the latter technique, we recently modified the vital lanthanum probe technique and by minimizing reperfusion effects were able to demonstrate differences in sarcolemmal permeability between hearts probed at the end of the ischaemic and reperfusion periods respectively (Harper and Lochner, 1989). In this model we found that the subendocardial sarcolemma became permeable to lanthanum after only 15 minutes of NICA.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Otherwise, after 40 minutes of ischemia, sodium continues to increase during reperfusion. Harper and Lochner [27] found that after 25 minutes of normothermic ischemia, isolated rat hearts did not recover sarcolemmal permeability, ultrastructure, or function. Malloy and coauthors [24] also observed that the recovery of myocardial function correlated with the return of intracellular sodium levels (measured by NMR) to baseline during reperfusion.…”
Section: Nmr Sodium Datamentioning
confidence: 99%
“…The latter may be of special interest on the basis of the concept that ischemic myocytes may enter a reversible phase before irreversible injury occurs (12,25).…”
Section: Introductionmentioning
confidence: 99%